ETHNOTOXIC PROFILE OF POISONOUS PLANTS OF KAGHAN VALLEY WESTERN HIMALAYAS PAKISTAN - S. Kayani; M. Ahmad; M. Hussain2; M. Zafar; M. A. Khan; G. M. Shah (Journal of Animal and Plant Sciences, 2017)
Rich accessibility of medicinal plants in the study area provides low cost health care for various ailments to local communities. This research report survey was commenced with an aim to document ethnic knowledge regarding the use of folk herbal medicine for various diseases among the local communities of Kaghan Valley. Rapid Appraisal Approach (RAA), semi-structured interviews, personal observations, group discussion with local people and meetings with herbalist were accompanied to acquire ethnomedicinal information. The current study recorded 62 poisonous plants belonging to 60 genera and 36 families. Which was reported by 243 informants (87 females, 137 males and 19 herbal specialists) from research area. The major uses of poisonous plants recorded from area were fish poison, antilice, anthelmintic, abortifacient, antiseptic, purgative and larvicides. Family Solanaceae was the most frequently used family with 6 reported medicinal plants followed by Euphorbiaceae, Papilionaceae and Ranunculaceae (4 each). The major source of herbal medicines was wild herbs (67.74%) followed by wild shrubs (22.58%) and trees (9.67). In plant part used, the whole plant (40.32%) and leaves (25%) were most dominant followed by root (16.12%) and seeds (10 %).
Keywords: Folklore; poisonous plants; Chemical constituents; Kaghan Valley; Pakistan